2018
DOI: 10.1002/jsde.12179
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Dynamic Surface Properties of Cationic/Anionic Surfactant Mixtures Based on Carboxylate Gemini Surfactant

Abstract: The equilibrium and dynamic surface properties of cationic/anionic surfactant mixtures of carboxylate gemini surfactant (CGS12) and quaternary ammonium salts with different alkyl chain lengths were investigated, and the synergistic properties and solubilization capacity toward phenanthrene of these mixtures were evaluated. Results show that all cationic/anionic surfactant mixtures exhibit negative interaction parameters, indicating the strong synergistic effects in the reduction of surface tension and the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…It is observed that the surface tension decreases rapidly at low demulsifier concentrations, and then has a nearly constant value, indicating the formation of micelles. The intersection of the two straight lines in the γ‐lgC plots is defined as the critical micelle concentration (CMC) . With the increase in the PPDA concentration, the PPDA molecules aggregate into micelles and the interaction between the molecules finally reaches equilibrium, so that the surface tension reaches a nearly constant value.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the surface tension decreases rapidly at low demulsifier concentrations, and then has a nearly constant value, indicating the formation of micelles. The intersection of the two straight lines in the γ‐lgC plots is defined as the critical micelle concentration (CMC) . With the increase in the PPDA concentration, the PPDA molecules aggregate into micelles and the interaction between the molecules finally reaches equilibrium, so that the surface tension reaches a nearly constant value.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when mixed, the two hydrophilic head groups with heterogeneous charges will produce strong electrostatic interaction, which will significantly reduce the electrostatic repulsion between molecules in the mixed monolayer and mixed micelles, increase the saturated adsorption capacity of surfactants and greatly improve the surface activity. [1][2][3][4][5] In addition, this interaction drives the hydrophilic head groups of anionic and cationic surfactants to associate closely to form a phospholipid-like structure so that it can self-assemble into rich aggregate structures such as vesicles without any external work. [6][7][8] However, excessive strong interaction will also make anionic and cationic surfactants form catanionic surfactant complex (precipitate) difficult to dissociate, thus losing surface activity and affecting its further application in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Demulsifiers are usually amphiphilic compounds that have both hydrophobic and hydrophilic groups. They can break down the oil‐in‐water emulsions by replacing the intrinsic interface active materials on the interface and changing the surface wettability of the solid particles to promote the coalescence and flocculation of the oil droplets . Demulsifiers can be divided into three categories of the anionic, cationic, and nonionic demulsifiers.…”
Section: Introductionmentioning
confidence: 99%